Synthesis and Application of Hydrophobically Associating Cationic Polyacrylamide: A Review - Sun, Y.J.; Zheng, H.L.; Tan, M.Z.; Ma, J.Y.; Fan, W.; Liao, Y. (Asian Journal of Chemistry, 2014)
The progress using micellar polymerization to synthesize an effective hydrophobically associating cationic polyacrylamide for treatement of wastewater was reviewed. Special emphasis was put on its preparation condition and reaction mechanism, as well as the applicability of dealing with some typical polluted water from paper making industry and oil contamination. Based on discussions above, future research perspectives on its synthesis and application were proposed.